Corruption and entrepreneurship : testing the theory of planned behavior - Heydari, Mohammad (London : Routledge, Taylor & Francis Group, 2024)
This book examines corruption as a collective behavior problem for entrepreneurs. In particular, it considers Azjen's theory of planned behavior (TPB) to explain perceived corruption and its effects on entrepreneurship. Heydari argues that behavioral intentions are shaped by variables such as attitude, subjective norms and perceived behavioral control. He proposes the novel Heydari Behavioral Synthesis Theory (HBST) model and applies it to two case studies to highlight the institutional, individual and societal factors that may inhibit entrepreneurial behavior. He concludes that corruption may persist not just because of difficulties in monitoring and prosecuting, but because it is systemically pervasive and discourages individual countermeasures. He closes by looking at anti-corruption policies and outlining future research directions. Arguing that widespread corruption may be theoretically mischaracterized in the literature, this book is of interest to policy-makers, researchers and postgraduate students in the fields of management science, industrial and organizational psychology, entrepreneurship and corruption studies.
1. Introduction to the Theory of Planned Behavior2. Methodology3. From Intention to Action: Application of the Theory to a Case Study 4. Moderators in the Theory of Planned Behavior 5. Greasing or Sanding the Wheels? 6. Corruption as a Collective Behavior 7. Corruption as a Collective Action Problem and Policy Implications 8. Extension and Empowerment of the Theory
Keywords: Political corruption; Entrepreneurship; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Organizational Behavior